Seventh Five Year Plan Mid-Term Appraisal Transport Sector Railways - Planning Commission (Planning Commission, 1987)
The Mid-Term Appraisal of the Transport Sector's Railways under the Seventh Five Year Plan highlights significant operational improvements, with freight traffic increasing by a target of 340 million tonnes. Key priorities include the replacement of overaged assets and modernization of rail infrastructure, requiring an estimated outlay of Rs. 16,517 crores. Performance metrics show enhanced productivity, with wagon utilization reaching record levels. However, challenges remain, notably excess manpower and outdated rolling stock, alongside a growing demand for passenger services at the expense of freight efficiency. Addressing these issues is critical for the Indian Railways to maintain its pivotal role in the national transport ecosystem.
Planning Commission Transport Division
Planning Commission Transport Division
Keywords: Importance of Railways; Capacity Constraints; Seventh Plan Priorities; Financial Overview; Performance Indicators; Operational Improvements; Identified Issues; Future Projections